The Impacts of Lockdown Policies on International Trade in the Philippines - Arenas, Guillermo Carlos (World Bank, Washington, DC, 2022)
The Philippines was among the most infected countries in East Asia at the onset of the COVID-19 outbreak. This study analyzes how international trade on various margins was affected by the country’s own lockdown policies and those of trading partners. Using a monthly series of product-by-country data for the period from January 2019 to December 2020 and an event study design, the paper shows that domestic lockdown measures did not affect international trade but external lockdowns affected both ex- ports and imports. The introduction of lockdown measures by trading partners affected imports more than exports, leading to 7 and 56 percent monthly average drops in export and import values, respectively. Restrictions on internal movements and international travel controls in partner countries were responsible for the drop in exports. The slump in imports was because of workplace closure, stay-at-home requirements, restrictions on internal movement, and international travel controls by trading partners of the Philip- pines. Intermediate goods were the key driver of the drop in imports following foreign lockdowns, reflecting supply disruptions in backward global value chain participation. At the same time, exports of intermediate goods were more resilient to the lockdown policies. Finally, both exports and imports were more affected at the extensive margin than the intensive margin, as lockdown measures hindered interactions among people, in turn reducing the potential of businesses to create new relationships and launch new products in foreign markets. Overall, diversified and geographically dispersed suppliers can help countries adjust better to future disruptions.